Website Based E-Commerce Waste Recycling Products - Setyorini Setyorini; Syarif Hidayatullah; Ike Kusdyah Rachmawati (Procedia of Engineering and Life Science, 2021)
The use of websites and social media as sales engines has begun to develop in line with the advancement of e-commerce. The waste bank is a waste material resource that can be recycled and made into a usable product whose existence has been ongoing until now but does not yet have an online promotional media that suits your needs. Creating a website that is in accordance with the intended flow of needs so that the website can make it easier for waste bank managers to widely market recycled products and reach consumers nationally. Especially at the Garbage Bank Recycling Product Gallery, Mojo Sari village, Malang Regency. The waste bank recycling e-commerce website created will be able to solve customer service problems that have been complained of. The impact is the increased level of customer satisfaction with ease of viewing product information, ease of ordering, and payment processing.